2019
DOI: 10.1186/s12917-019-2090-7
|View full text |Cite
|
Sign up to set email alerts
|

Specific detection and differentiation of classic goose parvovirus and novel goose parvovirus by TaqMan real-time PCR assay, coupled with host specificity

Abstract: BackgroundClassic goose parvovirus (cGPV) causes high mortality and morbidity in goslings and Muscovy ducklings. Novel GPV (N-GPV) causes short beak and dwarfism syndrome (SBDS) in Cherry Valley ducks, Pekin ducks and Mule ducks. Both cGPV and N-GPV have relatively strict host specificity, with obvious differences in pathogenicity. Specific detection of cGPV and N-GPV may result in false positives due to high nucleotide similarity with Muscovy duck parvovirus (MDPV). The aim of this study was to develop a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Earlier studies reported the possible vertical transmission of classic GPV in geese [ 19 ] and for MDPV [ 20 ]. Similarly, vertical transmission of NGPV from breeder cherry valley, pekin and mule ducks to their offspring was evidenced [ 17 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies reported the possible vertical transmission of classic GPV in geese [ 19 ] and for MDPV [ 20 ]. Similarly, vertical transmission of NGPV from breeder cherry valley, pekin and mule ducks to their offspring was evidenced [ 17 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zadori et al (1995) previously de ned a primer set for the VP3 position [8], which has been extensively used to identify and classify GPV elsewhere [6,30,31]. Since then, additional methods have been developed such as Real Time PCR [32], LAMP [33] and immunochromatographic assay [34]. We de ned a novel degenerated primer set for the detection of GPV amplifying VP3 coding sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional methods used to detect GPV infection include detecting the GPV antigen or antibodies against GPV. Among GPV antigen detection methods, electron microscopy observations, polymerase chain reaction (PCR), real-time PCR, matrix-assisted laser desorption/ionization-time of flight mass spectrometry, loop-mediated isothermal amplification, and recombinant polymerase amplification combined with the vertical flow have been established to detect GPV (Wan et al, 2019). However, these techniques are more appropriate for laboratory analysis and are not relevant for field practice, as they are time-consuming methods that require specialized systems and trained personnel.…”
Section: mentioning
confidence: 99%